TeAChnology in Science 5 (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
The present study employed a one-group pre-test-post-test research design to investigate the impact of utilizing validated video lessons as an intervention tool to enhance the performance level of fifth-grade learners in Science.  The researcher designed a comprehensive assessment test, which underwent rigorous validity and reliability testing, and administered it as a pretest and post-test to the selected participants.  The study participants were purposively sampled from the fifth-grade class, considering the researcher's teaching assignment and the feasibility of the study.  Ethical standards were strictly followed, including obtaining permissions and ensuring privacy, anonymity, and voluntary participation. Statistical analysis was conducted using the weighted mean to gauge learners' performance levels before and after the intervention, and the t-test was employed to ascertain the significance of the performance level difference.  The findings were presented through tables and interpreted in the context of relevant correlative studies. Initially, the pre-test results revealed that the average performance level of the grade 5 learners in Science stood at 49%, indicating an average level of mastery based on the National Education Testing and Research's Mastery/Achievement Level.  By analysing specific learning competencies in Quarter 1, the participants scored 60% in material usage, 42% in investigating material changes under different conditions, and 43% in designing valuable products from local, recyclable materials.  Subsequently, the post-test results demonstrated a noteworthy increase in learners' performance levels, with percentages of 72%, 64%, and 64% for the corresponding learning competencies.  The mean difference between the pretest and post-test was calculated at 9.133, accompanied by a t-value of 13.671 and a p-value of 0.000, indicating a significant improvement in learners' performance levels.  The learners attested to the usefulness of the intervention through video lessons, appreciating the explanatory nature of the videos, the provision of Filipino language subheadings, the flexibility of pausing and resuming, and the guidance from their parents/guardians.  The validity assessment of the TeACh videos yielded a highly valid average mean score of 4.76. The study's results suggest that implementing video lessons as an instructional intervention effectively enhanced the performance levels of learners in the Science domain.  While the TeACh videos proved beneficial for improving mastery and achievement of learning competencies, it is noted that their applicability may be limited to certain conditions, such as the availability of smartphones and flash drives, regions with inadequate internet connectivity, and proficiency in utilizing technological tools. In conclusion, using video lessons as an intervention strategy in the study substantially enhanced learners' performance in Science.  The findings advocate for integrating video lessons to improve instructional efficacy, although the specific context and conditions for their use should be carefully considered.  However, a notable limitation of this study lies in the restricted generalizability of the TeACh videos, which might not be universally applicable due to technological and access constraints, suggesting the need for further research to explore broader implementation scenarios.
Keywords: Video lessons; teachnology; science